Developing HRM Practices to Support Delegation: An Action Research Study in a SMEs - Rahman Hakim, Muhammad Fais; Marwansyah, Marwansyah; Pratami, Eggi Indriani (International Journal of Management Science and Information Technology, 2026)
his Action Research was conducted in a partner company, an SME operating in the business-to-business (B2B) industrial supply sector, where operational coordination, decision-making, and daily problem-solving remained highly dependent on the owner. This dependency constrained effective delegation and limited the owner's ability to focus on strategic responsibilities. This study aimed to develop Human Resource Management (HRM) practices to support structured delegation while examining their initial contribution to operational performance. A qualitative Action Research approach was employed through four stages: constructing, planning action, taking action, and evaluating action. The intervention focused on developing job analysis, job design, and a structured delegation mechanism. Data were collected through observations, semi-structured interviews, and company operational records. The findings indicate that the intervention established clearer work structures, strengthened role clarity, expanded delegated operational responsibilities, and reduced the owner's direct involvement in routine operations. Although the implementation period was insufficient to demonstrate substantial improvements across all operational performance indicators, early improvements were observed in delegation capability and operational responsiveness. These findings suggest that developing HRM practices provides the organizational foundation for effective delegation, enabling SME owners to shift their attention from daily operations to strategic decision-making and long-term business development.
Keywords: Human Resource Management; Delegation; Action Research; SME; Operational Performance